A Compact Circularly Polarized Planar Spiral Antenna With Ultrawide Bandwidth and Directional Radiation Pattern - Junlong Li; Yiming Zhang; CaiLi Yu; Guogang Huang; Hui Liu (International Journal of Antennas and Propagation, 2024)
A compact circularly polarized (CP) planar spiral antenna with ultrawide bandwidth and directional radiation pattern is proposed for ultra-wideband (UWB) positioning applications. The proposed antenna consists of a dual-arm planar spiral with a tapered microstrip line, two L-shaped metallic shorting stubs, and a square ground plane with four stepped slots. By connecting two L-shaped metallic stubs to both the ends of the dual-arm spiral through metal posts, the traveling wave current path is effectively extended, resulting in a significant improvement of the CP bandwidth. Additionally, both impedance bandwidth and circular polarization performance of the proposed antenna can be enhanced by adopting four stepped slots on the square ground plane. Measured results show that the planar spiral antenna features an impedance bandwidth from 3.23 GHz to 7.0 GHz (more than 73.7%), a 3-dB axial ratio (AR) bandwidth of 62.1% (3.05 GHz–5.8 GHz), and finally achieves an overlapping bandwidth of 56.9% (3.23 GHz–5.8 GHz). On the overlapping bandwidth, this antenna maintains a gain consistently above 6 dBic while the peak gain reaches about 7.4 dBic. The overall size of the antenna is 0.59λg × 0.59λg × 0.17λg (λg is the free-space wavelength at the lowest frequency, 3.23 GHz). Thanks to the ultrawide CP bandwidth and compact size, the proposed antenna can be a promising candidate for UWB positioning applications.